KINARA BUMDes: Enhancing Management Strategies for Community Prosperity - Sahara, Nyimas Ifada; Choiriyah, Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2024)
This study employs qualitative descriptive methods, utilizing observation, interviews, and documentation to investigate the management of Kinara BUMDes in Kemiri Village, Sidoarjo Regency, through the lens of management theory by George R. Terry. Despite facing challenges induced by the COVID-19 pandemic, the village government demonstrated resilience in planning, reinvigorating Kinara BUMDes through new management units. The organizational structure was efficiently organized, ensuring a well-defined division of labor and effective communication. Results indicate successful actuation in achieving organizational goals and meticulous supervision, promoting transparency at all levels of society. The study emphasizes the adaptability and strategic planning of rural economic units, offering insights for global scholars interested in sustainable rural development practices. Highlight : Strategic Planning: Despite the challenges posed by COVID-19, the study highlights the ability of Kinara BUMDes to adapt and revitalize through strategic planning, showcasing resilience in the face of unforeseen circumstances. Organizational Efficiency: The research underscores the importance of well-organized structures within BUMDes, emphasizing a clear division of labor, effective communication, and efficient supervision as crucial elements for achieving organizational goals. Transparency for Community Engagement: The findings reveal a commitment to transparency, ensuring that all activities conducted by Kinara BUMDes are accessible to and understood by all levels of society, fostering community engagement and support. Keywords: Rural Economic Units, BUMDes Management, Sustainable Development, COVID-19 Resilience, Organizational Transparency